Our Cause By Shri C. R. Pattabhi Raman Union Deputy Minister for Labour & Employment and Planning Broadcast—Madras A.I.R.—2-3-63 - Planning Commission (Planning Commission Government of India, 1957)
In his address “Our Cause,” Shri C. R. Pattabhi Raman emphasizes the critical role of planned economic development in achieving sustainable political and economic freedom in post-independence India. Highlighting achievements from the first decade of planning, including growth in national income, industrial output, agriculture, power generation, and transport, he underscores the need for long-term strategies focusing on heavy and basic industries. In light of external threats, particularly Chinese aggression, he stresses linking economic mobilization to defense requirements while maintaining civilian needs. Key priorities include enhancing labor productivity, promoting voluntary community work, and pursuing austerity measures to support national objectives. The address advocates a collective citizen effort, fiscal responsibility, and a resilient, self-reliant economy to ensure national security and equitable development.
Government of India Planning Commission
Keywords: Planned Development; Economic Freedom; Political Freedom; Industrial Growth; Agricultural Enhancement; National Defense; Labor Productivity; Voluntary Work; Austerity Measures; Self-Reliance; Infrastructure Development; Citizen Responsibility